FRI0133 FILGOTINIB, A SELECTIVE JANUS KINASE 1 (JAK1) INHIBITOR, MODULATES DISEASE-ASSOCIATED CYTOKINES IN PATIENTS WITH ACTIVE RHEUMATOID ARTHRITIS. (June 2019) - Taylor, Peter C.; Elboudwarej, Emon; Wanying, LI; Hawtin, Rachael E.; Liu, Jinfeng; Mirza, Amer M.
Abstract : Background: Filgotinib (FIL), an oral selective JAK1 inhibitor, was safe and effective in FINCH2, a randomized, double-blind, placebo-controlled, phase 3 study in patients with active rheumatoid arthritis (RA) who had an inadequate response to biologic disease-modifying anti-rheumatic drugs (bDMARDs). 1 Objectives: A longitudinal study of cytokines from patients in FINCH2 was conducted to identify RA-associated biomarkers related to bone biology, immune cell migration, and inflammation that are altered by FIL therapy; and FIL-associated biomarkers that correlated with clinical response (DAS28 [CRP], swollen and tender joint counts, pain, and fatigue). Methods: Plasma, serum, and urine samples from RA patients (n=449) who received FIL (100 mg, 200 mg) or placebo (PBO) once daily plus methotrexate were analyzed at baseline (BL) and week 12 for 42 disease-relevant cytokines using validated, commercially available single or multiplex assays. PBO-corrected on-treatment changes in cytokine levels from BL to week 12 were compared between treatment arms (Wilcoxon rank sum test). Spearman rank correlation was used to compare changes in cytokine level from BL to week 12 and clinical response. P-values <0.05 were considered significant. Results: At week 12, 18 of 42 cytokines significantly decreased with FIL 100 mg treatment relative to PBO; FIL 200 mg decreased these cytokines to a similar or greater degree. An additional 6 cytokines were significantly decreased by FIL 200 mg. Conversely, 2 cytokines increased relative to PBO with FIL 100 mg, and 5 cytokines increased with FIL 200 mg (sIL-6R, IL-10, IL-2, leptin, and IL-17A). Biomarkers most significantly modulated by FIL 200 mg (p<0.0001) included markers related to bone biology (MMP1 [–22.8%], MMP3 [–24.7%], CTX1 [–27.4%], and NTX [–16.4%]), immune cell migration (VCAM1 [–20.0%], ICAM1 [–14.2%], CXCL13 [–45.0%], and CXCL10 [–32.3%]), and inflammation (TNFRI [–20.7%], CRP [–77.4%], SAA [–61.8%], IL-6 [-13.6%], and resistin [–20.2%]). Hierarchical clustering of BL biomarker levels revealed distinct groups of cytokines that were strongly correlated with each other. Among them, SAA, IL-6, and CXCL10 were significantly positively correlated with each other (rho >0.6) and with RA disease activity (DAS28[CRP]) at BL (rho > 0.3). Biomarkers, including CRP (IL-6, SAA), PainVAS (CRP, SAA), and SJC28 (CRP, IL-6, CXCL10), were also significantly correlated with individual components of DAS28[CRP]. Several biomarkers associated with RA disease activity at BL were decreased with FIL at week 12 relative to PBO (FIL 100 mg: CRP [–48.7%], SAA [–36.9%], and IL-6 [–2.6%]; and FIL 200 mg: CRP [–77.4%], SAA [–61.8%], IL-6 [–13.6%], and CXCL10 [–32.3%]), suggesting FIL impacts these disease activities at a molecular level. Conclusion: Twelve weeks of FIL treatment significantly reduced 24 disease-relevant cytokines associated with bone biology, immune cell migration, and inflammation in patients with active RA. These effects were dose-dependent and suggest a shift toward a restored immune homeostasis. These findings are consistent with the clinical efficacy of FIL in FINCH2. References: [1] Genovese MC, et al. ACR 2018. Abstract L06. Disclosure of Interests: Peter C. Taylor Grant/research support from: Celgene, Galapagos, Eli Lilly, UCB, Consultant for: AbbVie, Galapagos, Gilead, Eli Lilly, Pfizer Inc, Emon Elboudwarej Shareholder of: Gilead Sciences, Inc., Employee of: Gilead Sciences, Inc., Wanying Li Shareholder of: Gilead Sciences, Inc., Employee of: Gilead Sciences, Inc., MyoKardia, Rachael E. Hawtin Shareholder of: Gilead, Employee of: Gilead, Jinfeng Liu Shareholder of: Gilead Sciences, Inc., Roche, Employee of: Gilead Sciences, Inc., Amer M. Mirza Shareholder of: Gilead Sciences, Inc., Employee of: Gilead Sciences, Inc.